2017
DOI: 10.1261/rna.065219.117
|View full text |Cite
|
Sign up to set email alerts
|

Pre-mRNA processing includes N6 methylation of adenosine residues that are retained in mRNA exons and the fallacy of “RNA epigenetics”

Abstract: By using a cell fraction technique that separates chromatin associated nascent RNA, newly completed nucleoplasmic mRNA and cytoplasmic mRNA, we have shown (Ke et al. 2017) that residues in exons are methylated (m 6 A) in nascent pre-mRNA and remain methylated in the same exonic residues in nucleoplasmic and cytoplasmic mRNA. Thus, there is no evidence of a substantial degree of demethylation in mRNA exons that would correspond to so-called "epigenetic" demethylation. The turnover rate of mRNA molecules is fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 51 publications
3
59
0
Order By: Relevance
“…These authors concluded that once m 6 A is formed, it is not subsequently removed. Their reanalysis nearly 35 years after their initial study came to the same conclusion [44]. Their reanalysis nearly 35 years after their initial study came to the same conclusion [44].…”
Section: Inconsistencies With M 6 a As The Substrate Of Ftomentioning
confidence: 72%
See 1 more Smart Citation
“…These authors concluded that once m 6 A is formed, it is not subsequently removed. Their reanalysis nearly 35 years after their initial study came to the same conclusion [44]. Their reanalysis nearly 35 years after their initial study came to the same conclusion [44].…”
Section: Inconsistencies With M 6 a As The Substrate Of Ftomentioning
confidence: 72%
“…Darnell and colleagues replicated this finding more recently using more sensitive m 6 A-detection methods and m 6 A mapping techniques [43]. Their reanalysis nearly 35 years after their initial study came to the same conclusion [44]. It should be noted that their inability to detect m 6 A loss from mRNA does not exclude the possibility that m 6 A demethylation is elicited by some type of signal that was not used in their assays.…”
Section: Inconsistencies With M 6 a As The Substrate Of Ftomentioning
confidence: 89%
“…Despite the recent fervor and debate surrounding the role of RNA modifications in mRNA , the presence of a multitude of modifications has long been known in tRNA. Early enzymatic digests of calf liver RNA showed mononucleotides that did not correspond to the four canonical RNA bases .…”
Section: Trna Modificationsmentioning
confidence: 99%
“…levels remaining unchanged in the three cellular compartments studied and by extension proposed that quantitatively little methylation or demethylation occurs on cytoplasmic mRNA. This view is at odds with the idea of m 6 A being a dynamic modification and is currently a matter of debate [16][17][18].…”
Section: Rna Structurementioning
confidence: 99%